Distinguishing the progression of an endometrioma: Benign or malignant?. (November 2018) - Bastu, Ercan; Onder, Semen; Demiral, Irem; Ozsurmeli, Mehmet; Keskin, Gulsah; Takmaz, Ozguc; Ozaltin, Selin; Gorgen, Husnu; Gungor, Mete; Yavuz, Ekrem; Buyru, Faruk
Abstract: Objective: To elucidate the immunohistochemical (IHC) differences of endometrioma tissues that may have the potential to progress to ovarian clear cell carcinoma (OCCC) by using KRAS, HNF1β, PIK3CA, PPP2R1A, and ARID1A as biomarkers. Study design: This is a retrospective clinical study, which was conducted in an university hospital. The groups comprised 14 patients with endometrioma resection who later developed OCCC (non-healthy endometrioma-case group) and 66 patients with endometrioma resection who did not develop ovarian cancer in subsequent follow-ups (healthy endometrium-control group). IHC staining with KRAS, HNF1β, PIK3CA, PPP2R1A, and ARID1A antibodies was performed in paraffin blocks of endometriomas obtained in both groups. For KRAS, PIK3CA, PPP2R1A, and ARID1A, cell staining intensity on a scale from 0 (negative) to 3 (strongly positive), and for HNF1β, the percentage of stained cells (0–5) and the intensity of staining (0–3) were scored. Results: KRAS, HNF1β, PIK3CA, PPP2R1A, and ARID1A were overexpressed in the case group samples compared with the endometrioma samples in the epithelial cells, and ARID1A and KRAS in the stroma were overexpressed in the case group samples compared with the matched control samples. Conclusions: KRAS, HNF1β, PIK3CA, PPP2R1A, and ARID1A immunostaining scores in endometriomas previous to OCCC were significantly different than in endometriomas with no malignancy occurring in subsequent follow-ups, and were single predictors of OCCC. Hence, immunostaining with these biomarkers may be a method of identifying patients with endometrioma who have the potential to develop OCCC.